Cyclodextrin–polysaccharide-based, in situ-gelled system for ocular antifungal delivery - Fernández-Ferreiro, Anxo; Fernández Bargiela, Noelia; Varela, María Santiago; Martínez, Maria Gil; Pardo, Maria; Piñeiro Ces, Antonio; Méndez, José Blanco; Barcia, Miguel González; Lamas, Maria Jesus; Otero-Espinar, Francisco.J. (Beilstein Journal of Organic Chemistry, 2014)
Fluconazole was studied with two different hydrophilic cyclodextrins (hydroxypropyl-β-cyclodextrin (HPBCD) and sulfobutyl ether-β-cyclodextrin (SBECD)) for the formation of inclusion complexes. HPBCD and SBECD showed low cell cytotoxicity in human keratocytes as assessed by the label-free xCELLigence system for real-time monitoring. The fluconazole–HPBCD complex was incorporated into an ion-sensitive ophthalmic gel composed of the natural polysaccharides gellan gum and κ-carrageenan. This system showed good bioadhesive properties and effective control of fluconazole release.
Keywords: cyclodextrins; eye drops; fluconazole; hydroxypropyl-β-cyclodextrin; sulfobutylether-β-cyclodextrin

(untitled) - Miller, D. (Expert Opin. Pharmacother., 2013)

(untitled) - Keay, L. J.; Gower, E. W.; Iovieno, A.; Oechsler, R. A.; Alfonso, E. C.; Matoba, A.; Colby, K.; Tuli, S. S.; Hammersmith, K.; Cavanagh, D.; Lee, S. M.; Irvine, J.; et al. (Ophthalmology, 2011)

Keratitis - Mravii, I.; Dekaris, I.; Gabri, N.; Romac, I.; Glavota, V.; Mlinari, E. (InTech, 2012)

(untitled) - Kathiravan, M. K.; Salake, A. B.; Chothe, A. S.; Dudhe, P. B.; Watode, R. P.; Mukta, M. S.; Gadhwe, S. (Bioorg. Med. Chem., 2012)

(untitled) - Pfaller, M. A.; Diekema, D. J.; Sheehan, D. J. (Clin. Microbiol. Rev., 2006)

(untitled) - Gratieri, T.; Gelfuso, G. M.; de Freitas, O.; Rocha, E. M.; Lopez, R. F. V. (Eur. J. Pharm. Biopharm., 2011)

(untitled) - Pawar, P.; Kashyap, H.; Malhotra, S.; Sindhu, R. (BioMed Res. Int., 2013)

(untitled) - Achouri, D.; Alhanout, K.; Piccerelle, P.; Andrieu, V. (Drug Dev. Ind. Pharm., 2013)

(untitled) - Kushwaha, S. K. S.; Saxena, P.; Rai, A. K. (Int. J. Pharm. Invest., 2012)

(untitled) - Liu, Z.; Li, J.; Nie, S.; Liu, H.; Ding, P.; Pan, W. (Int. J. Pharm., 2006)

(untitled) - Chen, X.; Li, W.; Zhong, W.; Lu, Y.; Yu, T. (J. Appl. Polym. Sci., 1997)

(untitled) - Coviello, T.; Matricardi, P.; Marianecci, C.; Alhaique, F. (J. Controlled Release, 2007)

(untitled) - Otero-Espinar, F. J.; Blanco-Méndez, J. (Curr. Top. Med. Chem., 2014)

Advances in Analytical Chemistry and Instrumentation - Higuchi, T.; Connors, K. A. (Phase-Solubility Techniques, 1965)

(untitled) - Anguiano-Igea, S.; Otero-Espinar, F. J.; Vila-Jato, J. L.; Blanco-Méndez, J. (Eur. J. Pharm. Sci., 1997)

(untitled) - Upadhyay, S. K.; Kumar, G. (Chem. Cent. J., 2009)

(untitled) - Kutyła, M. J.; Lambert, L. K.; Davies, N. M.; McGeary, R. P.; Shaw, P. N.; Ross, B. P. (Int. J. Pharm., 2013)

(untitled) - Nogueiras-Nieto, L.; Alvarez-Lorenzo, C.; Sandez-Macho, I.; Concheiro, A.; Otero-Espinar, F. J. (J. Phys. Chem. B, 2009)

(untitled) - Jansook, P.; Loftsson, T. (Int. J. Pharm., 2009)

(untitled) - Loftsson, T.; Stefánsson, E. (Acta Ophthalmol. Scand., 2002)

(untitled) - Kilic, C.; Girotti, A.; Rodriguez-Cabello, J. C.; Hasirci, V. (Biomater. Sci., 2014)

(untitled) - Niles, A. L.; Moravec, R. A.; Riss, T. L. (Expert Opin. Drug Discovery, 2008)

(untitled) - Xing, J. Z.; Zhu, L.; Gabos, S.; Xie, L. (Toxicol. In Vitro, 2006)

(untitled) - Chen, H.; Cui, L.; Jiang, X.-Y.; Pang, Y.-Q.; Tang, G.-L.; Hou, H.-W.; Jiang, J.-H.; Hu, Q.-Y. (Food Chem. Toxicol., 2012)

(untitled) - Kumar, S.; Karki, R.; Meena, M.; Prakash, T.; Rajeswari, T.; Goli, D. (J. Adv. Pharm. Technol. Res., 2011)

Hen’s Egg Test on the Chorioallantoic Membrane (HET-CAM) INVITTOX no. 96

(untitled) - Vallejo Diaz, B. M.; Perilla, J. E. (Rev. Colomb. Cienc. Quim.-Farm., 2008)

(untitled) - Siepmann, J.; Peppas, N. A. (Int. J. Pharm., 2011)

(untitled) - Otero Espinar, F. J.; Torres-Labandeira, J. J.; Alvarez-Lorenzo, C.; Blanco-Méndez, J. (J. Drug Delivery Sci. Technol., 2010)

(untitled) - Bibby, D. C.; Davies, N. M.; Tucker, I. G. (Int. J. Pharm., 2000)

(untitled) - Loftsson, T.; Hreinsdóttir, D.; Másson, M. (Int. J. Pharm., 2005)

(untitled) - Ramke, M.; Lam, E.; Meyer, M.; Knipper, A.; Heim, A. (Mol. Vision, 2013)

(untitled) - Xing, J. Z.; Zhu, L.; Jackson, J. A.; Gabos, S.; Sun, X.-J.; Wang, X.-b.; Xu, X. (Chem. Res. Toxicol., 2005)

(untitled) - Ceriotti, L.; Ponti, J.; Broggi, F.; Kob, A.; Drechsler, S.; Thedinga, E.; Colpo, P.; Sabbioni, E.; Ehret, R.; Rossi, F. (Sens. Actuators, B, 2007)

(untitled) - Fernández-Ferreiro, A.; González Barcia, M.; Gil Martínez, M.; Blanco Mendez, J.; Lamas Díaz, M. J.; Otero Espinar, F. J. (Farm. Hosp., 2014)

(untitled) - Blanco-Fuente, H.; Anguiano-Igea, S.; Otero-Espinar, F. J.; Blanco-Méndez, J. (Int. J. Pharm., 1996)

(untitled) - Lin, H.-R.; Sung, K. C. (J. Controlled Release, 2000)

(untitled) - Wu, H.; Liu, Z.; Peng, J.; Li, L.; Li, N.; Li, J.; Pan, H. (Int. J. Pharm., 2011)